Stellar rotation - Tassoul, Jean Louis (Cambridge astrophysics series ;, 2000)
Like the Earth and planets, stars rotate. Understanding how stars rotate is central to modelling their structure, formation and evolution, and how they interact with their environment and companion stars. This authoritative volume, first published in 2000, provides a lucid introduction to stellar rotation and the definitive reference to the subject. It combines theory and observation in a comprehensive survey of how the rotation of stars affects the structure and evolution of the Sun, single stars and close binaries. This book will be of primary interest to graduate students and researchers studying solar and stellar rotation and close binary systems. It will also appeal to those with a more general interest in solar and stellar physics, star formation, binary stars and the hydrodynamics of rotating fluids - including geophysicists, planetary scientists and plasma physicists.